2021
DOI: 10.21203/rs.3.rs-696505/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-Reported Symptom Study of COVID-19 Chemosensory Dysfunction in Malaysia

Abstract: Alterations in the three chemosensory modalities – smell, taste, and chemesthesis – have been implicated in Coronavirus Disease 2019 (COVID-19), yet emerging data suggest a wide geographic and ethnic variation in the prevalence of these symptoms. Studies on chemosensory disorders in COVID-19 have predominantly focused on Caucasian populations whereas Asians remain understudied. We conducted a nationwide, multicentre cross-sectional study using an online questionnaire on a cohort of RT-PCR-confirmed adult COVID… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The questionnaire was adapted from existing online questionnaires developed by the Global Consortium for Chemosensory Research (GCCR) (5) . The GCCR core questionnaire has been implemented in 10 languages as of April 18, 2020, and used or adapted in many other research studies (4,26,27) . Data collected included demographic information, COVID-19-related characteristics, and patient chemosensory situations, before and during infection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire was adapted from existing online questionnaires developed by the Global Consortium for Chemosensory Research (GCCR) (5) . The GCCR core questionnaire has been implemented in 10 languages as of April 18, 2020, and used or adapted in many other research studies (4,26,27) . Data collected included demographic information, COVID-19-related characteristics, and patient chemosensory situations, before and during infection.…”
Section: Methodsmentioning
confidence: 99%
“…There are reports that chemosensory disorders are important symptoms of COVID-19 infection (3–5) . Studies from the United States, Europe, Malaysia, and Singapore demonstrated that 12%– 88% of COVID-19-infected patients have olfactory and taste disorders (4,68) , while studies from China reported that 5%–25% of patients have smell and/or taste disorder (9,10) . The Omicron variant of SARS-CoV-2 was first detected in South Africa in November 2021, and became the main epidemic strain in the world by 15 January 2022 (11,12) .…”
Section: Introductionmentioning
confidence: 99%